Appearance of Thrombogenic Tendency Induced by Adrenaline and Its Prevention by β-Adrenergic Blocking Agent, Nialamide and Pyridinolcarbamate - Yamazaki, H; Sano, T; Odakura, T; Takeuchi, K; Matsumura, T; Hosaki, S; Shimamoto, T (Thrombosis and Haemostasis, 1971)
In 52 men and 33 women, the total, adhesive and nonadhesive platelet counts, onestage prothrombin time, euglobulinlysis time, and plasma nonesterified fatty acid were measured before and after an intravenous injection with 0.1 μg/kg of adrenaline or 1-noradrenaline. Three hours before the injection, placebo, 30 mg of phenoxybenzamine, 300 mg of pronethalol, 100 mg of nialamide or 100 mg of pyridinolcarbamate was administered orally under the double blind technique. Five minutes after the injection with adrenaline in 15 cases pretreated with placebo, a decrease in adhesive platelet count, and a shortening of one-stage prothrombin time and euglobulin lysis time were observed with statistical significance (P ˂ 0.01 ∼ 0.05). These changes were not observed in 15 cases injected with saline or noradrenaline. The changes were not observed in 10 cases pretreated with pronethalol, but were observed in 10 cases pretreated with phenoxybenzamine. So the effect of adrenaline may be due to stimulation of ß-adrenergic receptor sites. Meanwhile, the decrease in adhesive platelet count and the enhancement of blood coagulability were prevented by nialamide and pyridinolcarbamate, while the enhancement of fibrinolysis was not. The preventive effect of nialamide was less than that of pyridinolcarbamate. Phenoxybenzamine and nialamide prevented an increase in systolic blood pressure induced by adrenaline, and pronethalol prevented tachycardia by adrenaline, while pyridinolcarbamate did not affect these changes. Changes in plasma nonesterified fatty acid showed no relationship to the above hematological changes.